The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.4025/actasciagron.v43i1.48163
|View full text |Cite
|
Sign up to set email alerts
|

Screening of citrus scion-rootstock combinations for tolerance to water salinity during seedling formation

Abstract: Arid and semiarid regions are vulnerable to water deficits and salinity. Citrus plants are sensitive to saline stress and require the use of tolerant scion-rootstock combinations. Thus, this study aimed to evaluate and classify citrus scion-rootstock combinations with respect to their tolerance to salinity during seedling formation in a protected environment. An experiment was conducted in a randomized block design with a 5 x 12 x 2 factorial scheme corresponding to five levels of water salinity (0.8, 1.6, 2.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 13 publications
3
9
0
Order By: Relevance
“…Another inference that can be made is that, both in the first and the second year of cultivation, salinity negatively affected the production variables NFPL, WFPL, and AFW (Figure 7A,B); that is, as salinity increased, production decreased, corroborating what was shown in the boxplots presented in Figures 1-6, as well as in studies conducted by several authors [8,10,25,27].…”
Section: Production Analysissupporting
confidence: 85%
See 3 more Smart Citations
“…Another inference that can be made is that, both in the first and the second year of cultivation, salinity negatively affected the production variables NFPL, WFPL, and AFW (Figure 7A,B); that is, as salinity increased, production decreased, corroborating what was shown in the boxplots presented in Figures 1-6, as well as in studies conducted by several authors [8,10,25,27].…”
Section: Production Analysissupporting
confidence: 85%
“…The evaluation of the second production year made it possible to confirm the information obtained in the first year when the distinction of genotypes irrigated with waters of higher salinity levels was verified. The observations can be confirmed particularly for HTR-069, a hybrid of 'Pera' sweet orange with 'Yuma' citrange, as a rootstock that confers greater tolerance to salinity, corroborating the results obtained with this hybrid in the seedling formation stage [10]. On the other hand, highlighting this rootstock does not disqualify the potential of the others, since citrus plants show stabilization of production between six and seven years [15].…”
Section: Production Analysissupporting
confidence: 61%
See 2 more Smart Citations
“…Unfortunately, these widely planted varieties are particularly susceptible to HLB disease, with many Florida groves reaching 100% infection [23]. The choice of rootstock can play a role in many horticultural traits such as tree size, fruit yield, and fruit quality [25][26][27][28], as well as tolerance to salinity [29,30]. A recent survey of 'Hamlin' on 32 rootstocks in two locations with different soil types showed that the rootstock choice affected the severity of HLB foliar disease symptoms and sturdiness under storm-force winds [31].…”
Section: Introductionmentioning
confidence: 99%